Pengaruh Tingkat Bunga, Indeks Harga Saham Terhadap Harga Saham PT Telkom Berdasarkan Path Analysis (Penelitian Di Bursa Efek Indonesia) - Manurung, Elizabeth Tiur; Mulyawan, Sean Adi (Jurnal Administrasi Bisnis, 2009)
Capital market has important role in Indonesiaâs economy as a tool for governmentto maintain economic stability. Stock is one of many capital marketâs instruments.Stock price fluctiations can be seen from Composite Stock Price Index and SectoralStock Price Index. Stock price fluctuations is influenced by many factors. One ofthose factors is interest rate. The best approach to interest rate in Indonesia is the BIRate.Keywords: Capital market, Stock price, interest rate, Sectoral stock price index